Research on Intelligent Recognition and Control Device of Aviation Line Number. Issue 1 (February 2021) - Zhao, Changfu; Cao, Guohua; Ding, Hongchang; Zhang, Ying; Hou, Han
Abstract: In order to solve the problems such as low sorting efficiency, high error rate and inability to match the corresponding installation position on aviation wiring, we propose a machine vision line number recognition method, which is based on the threshold segmentation algorithm of gradation histogram to identify the line number and index the recognized results. The wire harness recognition system mainly includes three parts: wire number positioning, wire number character segmentation and character recognition. Experimental results show that the online detection speed of the vision system is 30m/min, the accuracy rate is higher than 98% and the average time is 0.04s. By matching the recognition results, index to the position where the wiring harness is to be installed to meet the requirements of aviation wiring.